The effect of sodium chloride on the formation of W/O microemulsions in soy bean oil/surfactant/water systems and the solubilization of small hydrophilic molecules - Polizelli, Marcos Alexandre [UNESP]; dos Santos, Andre Luis [UNESP]; Feitosa, Eloi [UNESP] (Elsevier B.V., 2008)
Partial pseudoternary phase diagrams were constructed for soy bean oil (SBO)/surfactant/NaCl aqueous solution systems, at 25 degrees C, using the anionic sodium bis(2-ethylhexyl) sulfosuccinate (ACT) and zwiterionic phosphatidylcholine (PC) or mixtures of these surfactants. The isotropic single phase of water-in-oil (W/O) microemulsions (MEs) is shown in the phase diagram and their viscosity reported. ME samples containing small amount of surfactant exhibit slightly higher viscosity than pure SBO, and were used in the solubilization of small water soluble molecules. NaCl enhances the area of the ME phase and MEs with different surfactant composition exhibit different induction time as obtained from tests of oxidative stability, and so are the MEs enriched with ascorbic acid, folic acid and FeSO4, with the latter exhibiting lower stability. The so prepared enriched soy bean oil has potential application in food industry since the surfactants are food grade. (C) 2007 Elsevier B.V. All rights reserved.
Keywords: microemulsions; Phase diagram; enriched soy bean oil; Surfactant; phosphatidylcholine; AOT; Rheology; scattering techniques